A New Law Enforcement Cooperation Model in Southeast Asia and an Examination of Its Global Application: A Korean Desk. (21st April 2019) - Jung, Jeyong; Lee, Chang‐Moo
Abstract : This paper aims to assess the efficacy of the "Korean Desks" in the Philippines and Vietnam and to investigate whether this new law enforcement cooperation model could be replicated globally. As a research method, in‐depth semi‐structured interviews were conducted with a total of six Korean police officers at the Korean Desks. Three themes emerged from the interview data. First, this cooperation model has increased the sense of public safety among Korean communities and has provided higher efficiency in police cooperation. Second, factors such as no preceding model to consider, demanding workload, and high dependency on local officers have been found to be difficulties in the operations of the Korean Desks. Third, it was argued that the application of this model to a different nation would face great challenges primarily due to the high variability of sociocultural structures across nations. Findings revealed that the Korean Desk model was deeply embedded in the sociocultural environment in which it was established, and the implementation of the model was contingent upon the officers' experiences rather than guidance from the police headquarters.